Herpes Zoster and Multiple Sclerosis. Issue 5651 (26th April 1969) - Lenman, J. A. R.; Peters, T. J.
Abstract : No significant difference was found between 50 consecutive patients with multiple sclerosis and matched controls in respect of previous infection with rubella or measles and chicken-pox, or of previous vaccination and immunizing injections. Significantly more patients had a past history of herpes zoster compared with the controls.